Moskva slezam ne verit . Moscow Does Not Believe in Tears - Menshov, Vladimir (Soviet Union, 1979)
Life story of three girlfriends from youth to autumn ages. Their dreams and wishes, love, disillusionment. Different careers. And great, late love.